THE FACEBOOK PARADOX: THE CREATION AND DESTRUCTION OF CYBER-HAPPINESS - Yusup, Heri (Fakultas Komunikasi, Sastra, dan Bahasa, 2017)
Social media based communication is one of milestones of dramatic changing in contemporary society. Many people obtain benefits of this rapid change of internet. For an example, social media is believed to be a way to improve the quantity and quality of social networks. However, social media still has its paradoxical sides; creating and destructing. This research aimed to analyze positive and negative sides of Facebook, one of the most used social media platforms. The present research applied theoretical framework of affordances and constraints of two contradictory sides of technology from Mc Luhan (Jones and Hafner, 2012). The findings show that Facebook has two innate paradoxical sides that have potentials to not only provide happiness to its users but also take it.